Корпоративная социальная ответственность как принцип ценностно ориентированного менеджмента - Буко, С. (Социология: теория, методы, маркетинг, 2006)
The author provides an overview of key tendencies in the corporate social responsibility (CSR) concept development, including Ukrainian experience. Definitions, development stages, and core structural elements of CSR are reviewed in the article from a perspective of value based management as to profitable international organizations. The author defines corporate social responsibility as a principle within a new stage of contemporary management where humanistic values prevail over pragmatic ones and lead to a new comprehension of business model in the world.